A CGRP receptor antagonist peptide formulated for nasal administration to treat migraine - von Mentzer, Bengt (J Pharm Pharmacol, 2020)
OBJECTIVES: To investigate the formulation of the peptide-based antagonist ((34)Pro,(35)Phe)CGRP(27–37), of the human calcitonin gene-related peptide (CGRP) receptor as a potential nasally delivered migraine treatment. METHODS: Peptide sequences were prepared using automated methods and purified by preparative HPLC. Their structure and stability were determined by LC-MS. Antagonist potency was assessed by measuring CGRP-stimulated cAMP accumulation in SK-N-MC, cells and in CHO cells overexpressing the human CGRP receptor. In vivo activity was tested in plasma protein extravasation (PPE) studies using Evans blue dye accumulation. Peptide-containing chitosan microparticles were prepared by spray drying. KEY FINDINGS: ((34)Pro,(35)Phe)CGRP(27–37) exhibited a 10-fold increased affinity compared to αCGRP(27–37). Administration of ((34)Pro,(35)Phe)CGRP(27–37) to mice led to a significant decrease in CGRP-induced PPE confirming antagonistic properties in vivo. There was no degradation of ((34)Pro,(35)Phe)CGRP(27–37) and no loss of antagonist potency during formulation and release from chitosan microparticles. CONCLUSIONS: ((34)Pro,(35)Phe)CGRP(27–37) is a potent CGRP receptor antagonist both in vitro and in vivo, and it can be formulated as a dry powder with no loss of activity indicating its potential as a nasally formulated anti-migraine medicine.